ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERMINTAAN KREDIT CEPAT AMAN OLEH MASYARAKAT DI PT PEGADAIAN CABANG KALIANYAR - lustiowati, lustiowati; Priyono, Joko (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2021)
This study aims to look at the variable of customer income, the number of customer dependents, and customer education level on demand for Secure Fast Credit (KCA). This research was conducted at PT Pegadaian Kalianyar Branch. The type of data used in this study using primary data. The data is collected through a list of questions (questionnaires) filled out by customers of the PT Pegadaian Kalianyar Branch. The samples in the study as many as 99 respondents using sampling techniques conducted by using the slovin formula. The method used in this study is quantitative and uses multiple linear analysis methods using SPSS 16 computer program. Based on the results of the estimates showed that the variable income of customers, the number of customer dependents, the level of education of customers positively and significantly on the demand for Secure Fast Credit PT Pegadaian Kalianyar Branch. Based on the results of the T-test variable customer income is the variable that most variables the demand for Secure Fast Credit at PT Pegadaian Kalianyar Branch with a value of 6,304 and a significant value of 0.000